High thermal conductivity polymer chains with reactive groups: a step towards true application. Issue 6 (27th August 2020) - Chen, Anqi; Wu, Yanyan; Zhou, Shaoxin; Xu, Wenxue; Jiang, Wenlong; Lv, You; Guo, Wei; Chi, Keyu; Sun, Qi; Fu, Tingting; Xie, Tingting; Zhu, Yuan; et al.
Abstract : Nanostructured polyethylene (PE, [–CH2 –CH2 –] n ) films with metal-like thermal conductivity have opened up opportunities for polymers in advanced thermal management. Abstract : Nanostructured polyethylene (PE, [–CH2 –CH2 –] n ) films with metal-like thermal conductivity have opened up opportunities for polymers in advanced thermal management. However, in practice, polymers used in thermal management are either thermosets or at least stable at high temperature, for which 150–180 °C is typical. Thus PE as a thermoplastic polymer, whose softening temperature is ∼120 °C, is not applicable in real use. Thus here we introduce a simple reactive group –OH to each segment of the PE chain [–CH2 –CH2 –] n, which turns the polymer into polyvinyl alcohol (PVA), as a step towards the thermo stable system. Our calculations show that for aligned PVA chains, the thermal conductivity can reach 8.49 W m −1 K −1 (infinite chains), and experiments verify this by achieving a thermal conductivity of 8.51 W m −1 K −1 in a PVA film consisting of chain-aligned nanofibers. The alignment degrees of the PVA chains in the nanofibers are especially investigated to elucidate the nanostructure of the film, and the phonon dispersion and transport are also discussed. This work is intended to stimulate a further trial into the development of high thermal conductivity polymer materials towards real uses and true application scenarios.